Type-2 Fuzzy Based Quadrotor Control Approach - Ilhan, Ismail; Karakose, Mehmet (Ieee, 2013)
Unmanned air vehicles has recently become applications that are being increasingly used in both unmilitary and military areas and that are popular fields of research. The quadrotor type among the unmanned air vehicles, which come in different types, sizes and models depending on their area of use, come into prominence with several advantages it offers. This study performs the modeling, simulation, altitude and direction controls by means of a type-2 fuzzy system of an unmanned air vehicle. A proper algorithm is required for a quadrotor due to the environmental conditions, uncertainty and noise effects. Therefore, type-2 fuzzy controller was preferred and the performance of type-2 controller was provided against the type-1 and PID control methods in the simulations were carried out in this study. Simulation results obtained in the study show the effectiveness of type-2 fuzzy controller over the other controllers.
9th Asian Control Conference (ASCC) -- JUN 23-26, 2013 -- Istanbul, TURKEY
Keywords: Type-2 fuzzy system; quadrotor; unmanned air vehicle; control system